Repertoire Denny Novita dan Transformasi Kisah Gajah Mada dan Pitaloka dalam Novel Kembang Seruni - Widihastuti, Rahma Ari (Sutasoma : Jurnal Sastra Jawa, 2020)
In the Kitab Pararaton, the relationship between Gajah Mada and Dyah Ayu Pitaloka does not describe a special relationship. However, there is a different meaning from the perspective of the reader which is then appreciated as a new work. This study aims to compare the story of Gajah Mada and Pitaloka in the Kitab Pararaton with "Kembang Seruni"; describe Denny Novita's repertoire in Kembang Seruni against the Kitab Pararaton; and describes the form of transformation made by the reader (Denny Novita) to the Gajah Mada-Pitaloka Kitab Pararaton in the novel 'Kembang Seruni'. The method used in this research is descriptive qualitative with Wolfgang Iser's literary reception theory and comparative literature. The results showed that; 1) there are similarities in the characters and plot in Denny Novita's Kitab Pararaton and Kembang Seruni, 2) Novita presents the story of Gajah Mada's forbidden love with Pitaloka very clearly. The story that does not appear in the Kitab Pararaton, even connects it in modern life, and 3) The story of Gajah Mada and Pitaloka is the main focus, that a brave patih who is able to conquer the archipelago is a human who has love. Key words: repertoire, transformation, pararaton, kembang seruni